Complex food webs coincide with high genetic potential for chemolithoautotrophy in fractured bedrock groundwater. (1st March 2020) - Herrmann, M.; Geesink, P.; Yan, L.; Lehmann, R.; Totsche, K.U.; Küsel, K.
Abstract: Groundwater ecosystems face the challenge of energy limitation due to the absence of light-driven primary production. Lack of space and low oxygen availability might further contribute to generally assumed low food web complexity. Chemolithoautotrophy provides additional input of carbon within the subsurface, however, we still do not understand how abundances of chemolithoautotrophs, differences in surface carbon input, and oxygen availability control subsurface food web complexity. Using a molecular approach, we aimed to disentangle the different levels of potential trophic interactions in oligotrophic groundwater along a hillslope setting of alternating mixed carbonate-/siliciclastic bedrock with contrasting hydrochemical conditions and hotspots of chemolithoautotrophy. Across all sites, groundwater harbored diverse protist communities including Ciliophora, Cercozoa, Centroheliozoa, and Amoebozoa but correlations with hydrochemical parameters were less pronounced for eukaryotes compared to bacteria. Ciliophora -affiliated reads dominated the eukaryotic data sets across all sites. DNA-based evidence for the presence of metazoan top predators such as Cyclopoida ( Arthropoda ) and Stenostomidae ( Platyhelminthes ) was only found at wells where abundances of functional genes associated with chemolithoautotrophy were 10–100 times higher compared to wells without indications of these top predators. At wells closer to recharge areas with presumably increased inputs of soil-derived substances and biota, fungi accounted for up to 85% of the metazoan-curated eukaryotic sequence data, together with a low potential for chemolithoautotrophy. Although we did not directly observe higher organisms, our results point to the existence of complex food webs with several trophic levels in oligotrophic groundwater. Chemolithoautotrophy appears to provide strong support to more complex trophic interactions, feeding in additional biomass produced by light-independent CO2 -fixation. Graphical abstract: Image 1 Highlights: Molecular analysis indicated diverse protist communities of multiple trophic levels. Ciliophora contributed the highest fraction of eukaryotic sequence reads. Molecular data suggest links between chemolithoautotrophy and metazoan top predators. High fractions of fungi coincided with low potential for chemolithoautotrophy.